Conversational repairs on Reddit: Widely initiated but often uncompleted - Alex Goddard; Alex Gillespie (PLoS ONE, 2025)
Conversational repair has been proposed as a universal system for maintaining mutual understanding during social interactions. The repair system has been studied extensively in offline synchronous interactions (e.g., face-to-face, phone calls) and has been observed across cultures and languages. However, the prevalence of conversational repairs is unclear in online asynchronous text-based interactions. Online interactions are increasingly important for public deliberation, and it is therefore important to understand how conversational repairs manifest in different online contexts. To address this gap, we conducted two analyses of Other-initiated repairs in 25 English-language Reddit communities (subreddits), covering a diverse range of topics and communication norms. Analysis 1 examines the frequency of repair initiations across subreddits, finding them to be widespread (in every subreddit) and frequent (58.48% of interactions experience a repair initiation). Analysis 2 examines the emergence of repairs, finding that a repair initiation becomes increasingly likely the longer a comments thread progresses (Median time-to-repair = 6 turns). These results suggest that the prevalence and emergence of repair initiations in online interactions are comparable to offline contexts. However, we also find 44.80% of initiations receive no reply, precluding the possibility of a repair completion. Thus, conservatively, nearly half of the repair initiations in our data went uncompleted. This suggests that the online medium alters the way initiations are completed compared to offline interactions. We discuss the implications of this finding and avenues for future research.